Hasil Penelitian Kecerdasan Adversitas dan Kemampuan adaptasi diri: Kecerdasan Adversitas dan Kemampuan Adaptasi Diri Mahasiswa di Masa Pandemi Covid-19 - Anik Puji Rahayu (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2021)
In the current Covid-19 pandemic, there is a process of major changes the result of social distancing policies for all people so that they must be able to adapt. Students must also adapt to changes in learning methods and have high morale so that they can continue to follow learning well. So students are required to have soft skills regarding the use of online learning model applications, preparing quotas, and being in an area that is sufficiently accessible to the internet network so that later there will be no obstacles when attending online lectures. Students must also adapt and have a fighting spirit to stay enthusiastic about learning. This research is a type of quantitative research, cross-sectional design with a descriptive-analytic approach. The sample was taken by random sampling technique of 200 respondents. as many as 175 people (88%). Talented respondents in the arts were 90 respondents (45%), sports were 70 respondents 35%), and other fields were 40 respondents (20%). The results of univariate analysis describe respondents with adversity quotient in the category climbers as many as 33 respondents (16.5%), the category campers obtained 163 respondents (81.5%) and the category quitters obtained 4 respondents (2%). Meanwhile, the frequency of self-adaptation ability was 193 respondents (96.5%) with the adaptive category and as many as 7 respondents (3.5%) in the maladaptive category. The results of the bivariate analysis showed that the Pv value was 0.001 less than the alpha value = 0.05, which indicated that there was a significant relationship between adversity quotient and the self-adaptation ability of students during the Covid-19 pandemic with a positive relationship with sufficient strength. Further researchers are expected to research to discuss the factors and characteristics of self-adaptation that are dominant to adapt to a new environment. Keywords: Adversity Quotient, self-adaptation ability, covid-19